Effects of cadmium and zinc interactions on the physiological biochemistry and enrichment characteristics of Iris pseudacorus - Xiaofang Yu; Yujia Liu; Linjie Yue; Xiaoxuan Zeng; Yuwei Huang; Hanyue Xue; Bin Xu; Junrui Zhang; Xue Xiao; Lijuan Yang; Ting Lei; Mingyan Jiang; et al. (Ecotoxicology and Environmental Safety, 2024)
Compound pollution with cadmium (Cd) and zinc (Zn) is common in nature. The effects of compounded Cd and Zn on the growth and development of Iris pseudacorus in the environment and the plant’s potential to remediate heavy metals in the environment remain unclear. In this study, the effects of single and combined Cd and Zn stress on I. pseudacorus growth and the enrichment of heavy metals in I. pseudacorus seedlings were investigated. The results showed that under Cd (160 μM) and Zn (800 μM) stress, plant growth was significantly inhibited and photosynthetic performance was affected. Cd+Zn200 (160 μM + 200 μM) reduced the levels of malondialdehyde, hydrogen peroxide, and non-protein thiols by 31.29%, 53.20%, and 13.29%, respectively, in the aboveground tissues compared with levels in the single Cd treatment. However, Cd+Zn800 (160 μM + 800 μM) had no effect. Cd and Zn800 inhibited the absorption of mineral elements, while Zn200 had little effect on plants. Compared with that for Cd treatment alone, Cd + Zn200 and Cd+Zn800 reduced the Cd content in aboveground tissues by 54.15% and 49.92%, respectively, but had no significant effect on Cd in the root system. Zn significantly reduced the Cd content in subcellular components and limited the content and proportion of Cd extracted using water and ethanol. These results suggest that a low supply of Zn reduces Cd accumulation in aboveground tissues by promoting antioxidant substances and heavy metal chelating agents, thus protecting the photosynthetic systems. The addition of Zn also reduced the mobility and bioavailability of Cd to alleviate its toxicity in I. pseudacorus.